2013
DOI: 10.1111/1365-2656.12070
|View full text |Cite
|
Sign up to set email alerts
|

Downstairs drivers ‐ root herbivores shape communities of above‐ground herbivores and natural enemies via changes in plant nutrients

Abstract: Summary 1.Terrestrial food webs are woven from complex interactions, often underpinned by plant-mediated interactions between herbivores and higher trophic groups. Below-and aboveground herbivores can influence one another via induced changes to a shared host plant, potentially shaping the wider community. However, empirical evidence linking laboratory observations to natural field populations has so far been elusive. 2. This study investigated how root-feeding weevils (Otiorhynchus sulcatus) influence differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 43 publications
1
44
1
Order By: Relevance
“…Second, lower nitrogen concentrations in the resprouting leaves may result in lower nutritional quality for insect herbivores (Mattson 1980). Herbivory can also affect leaf traits distant from the damaged site by changing resource allocation at the whole-plant scale (Gange and Brown 1989;Bezemer et al 2003;Johnson et al 2013). Johnson et al (2013) reported that root feeding weevils induced changes in aboveground plant nutrients (C, N, P, and amino acids) and defensive compounds (phenolics) of blackcurrant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, lower nitrogen concentrations in the resprouting leaves may result in lower nutritional quality for insect herbivores (Mattson 1980). Herbivory can also affect leaf traits distant from the damaged site by changing resource allocation at the whole-plant scale (Gange and Brown 1989;Bezemer et al 2003;Johnson et al 2013). Johnson et al (2013) reported that root feeding weevils induced changes in aboveground plant nutrients (C, N, P, and amino acids) and defensive compounds (phenolics) of blackcurrant.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several authors have reported that herbivory by one herbivore can positively or negatively affect other herbivores that are distant from the damaged site due to changes in resource allocation at the whole-plant scale (Gange and Brown 1989;Bezemer et al 2003;Johnson et al 2013). Regardless, previous studies have generally focused on particular plant parts either close to or distant from the damaged site (Roininen et al 1997;Bezemer et al 2003;Nakamura et al 2003;Johnson et al 2013). However, if the direction (positive or negative) and magnitude of plant-mediated effects differ between spatially separated plant parts, focusing only on a particular part would lead to under-or over-estimation of the effect at the whole-plant scale.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This increases survival, dissemination and spread of mainly the soil borne pathogens to areas that were not previously infected (Thompson et al, 2013). Fungal pathogens benefit from flood events compared to any other pathogens (Parvatha, 2015).…”
Section: Effect Of Extreme Weather Events On Insect Pests and Diseasesmentioning
confidence: 99%
“…The increase in frequency and intensity of extreme weather events, changes in moisture conditions, temperature rises and elevated carbon dioxide concentrations are expected to magnify pest pressure on agricultural systems through various ways (Johnson et al, 2013). Insect pests are likely to respond through range expansion of the existing insect pests, invasion by new insect pests and accelerated insect pest development (Parvatha, 2015).…”
Section: Introductionmentioning
confidence: 99%